2017
DOI: 10.4025/actascianimsci.v39i4.36692
|View full text |Cite
|
Sign up to set email alerts
|

<b>Carcass characteristics and sensorial evaluation of meat from Nellore steers and crossbred Angus vs. Nellore bulls

Abstract: ABSTRACT. This study evaluated animal performance, carcass characteristics and meat quality of 36-month old Nellore steers finished in pastures (n = 10) and 20-month old Angus vs. Nellore bulls finished in feedlot (n = 10). Final body weight, carcass weight, characteristics, conformation and fat thickness, were higher (p < 0.001) for the Nellore steers than for Angus vs. Nellore bulls. Water losses during chilling (24 hours, 4 o C) were lower (p < 0.05) for Nellore steers than for the Angus vs. Nellore bulls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
3
5
1
5
Order By: Relevance
“…According to the cooking loss test analysis, the present study found values ranging from 4 to 24.07% of total moisture loss, with an overall mean of 11.75%. Differently from the results obtained in this study, greater losses were observed by Barcellos et al [42] in cattle of the nelore breed in Panama, with moisture losses of 24% and 29% in Angus x Nelore crossbreeds. Andrade et al [4] found in cattle of the nelore breed greater losses of 29.1% when compared to the present study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…According to the cooking loss test analysis, the present study found values ranging from 4 to 24.07% of total moisture loss, with an overall mean of 11.75%. Differently from the results obtained in this study, greater losses were observed by Barcellos et al [42] in cattle of the nelore breed in Panama, with moisture losses of 24% and 29% in Angus x Nelore crossbreeds. Andrade et al [4] found in cattle of the nelore breed greater losses of 29.1% when compared to the present study.…”
Section: Resultscontrasting
confidence: 99%
“…A smaller lightness value represents a darker meat, which may be associated with the presence of fat, given that animals with higher content present higher reflectance [45], or even the breed, since the animals with a predominance of Nelore in their genotype presented darker meat, a behavior related to the agitated temper of the breed [5], another factor that could be attributed to the pH in the case of meat with low lightness, because meats with values higher or equal to 6.0 tend to have low light reflectance due to high water retention capacity [47]. In turn the a* and b* values are in accordance with the previous studies, such as Barcellos et al [42] for a* of 14.58 and Andrade et al [4] for b* of 3.78, all performed with cattle of the Nelore breed.…”
Section: Resultssupporting
confidence: 82%
“…On the contrary, a significant decrease was found for compression and energy among samples as ageing progressed for both production systems. These differences in the intensity of ageing between steers and bulls also seemed apparent in Barcellos et al ., 44 who found similar tenderness in LT muscle from steers after 4 days of ageing to that from bulls after 14 days of ageing.…”
Section: Resultssupporting
confidence: 65%
“…Taurine cattle have been used by Brazilian farmers in industrial crosses with zebu breeds due to increased gain in heterosis and complementarity of desirable traits, yielding the best results in meat production (Reggiori et al, 2016). Different crosses between Bos taurus taurus and Bos taurus indicus generate positive results for the efficiency of a production system, mainly in terms of carcass weight, yield of meat cuts, and meat tenderness (Barcellos et al, 2017). Santana et al (2013) described economic gains from the use of crosses in bioeconomic simulations with full-cycle and pre-weaning systems.…”
Section: Introductionmentioning
confidence: 99%